The importance of selecting a cruciate-retaining total knee prosthesis for a patient with a large physiological posterior tibial slope: a case report. Issue 12 (20th December 2022) - Yamamoto, Ayakane; Kaneko, Takao; Takada, Kazutaka; Yoshizawa, Shu
Abstract: For Japanese individuals, deep bending is inevitable in their daily lives, such as during seiza sitting and kneeling. Thus, achieving a good post-operative range of motion is an important factor in improving patient satisfaction. Even normal knees often have a posterior tibial slope of more than 10°. We report the case of a 76-year-old woman who underwent proximal tibial osteotomy at 8° with the Vanguard Knee cruciate retaining total knee arthroplasty (TKA) system. She required the revision TKA 10 years later due to ultra-high-molecular-weight polyethylene wear and breakage of the posteromedial tibial component.